Widespread six degrees Celsius cooling on land during the Last Glacial Maximum - Seltzer, Alan; Ng, Jessica; Aeschbach, Werner; Kipfer, Rolf; Kulongoski, Justin T.; Severinghaus, Jeffrey P.; Stute, Martin (Nature, 2021)
The magnitude of global cooling during the Last Glacial Maximum (LGM, the coldest multimillennial interval of the last glacial period) is an important constraint for evaluating estimates of Earth’s climate sensitivity1,2. Reliable LGM temperatures come from high-latitude ice cores3,4, but substantial disagreement exists between proxy records in the low latitudes1,5-8, where quantitative low-elevation records on land are scarce. Filling this data gap, noble gases in ancient groundwater record past land surface temperatures through a direct physical relationship that is rooted in their temperature-dependent solubility in water9,10. Dissolved noble gases are suitable tracers of LGM temperature because of their complete insensitivity to biological and chemical processes and the ubiquity of LGM-aged groundwater around the globe11,12. However, although several individual noble gas studies have found substantial tropical LGM cooling13-16, they have used different methodologies and provide limited spatial coverage. Here we use noble gases in groundwater to show that the low-altitude, low-to-mid-latitude land surface (45 degrees south to 35 degrees north) cooled by 5.8 ± 0.6 degrees Celsius (mean ± 95% confidence interval) during the LGM. Our analysis includes four decades of groundwater noble gas data from six continents, along with new records from the tropics, all of which were interpreted using the same physical framework. Our land-based result broadly supports a recent reconstruction based on marine proxy data assimilation1 that suggested greater climate sensitivity than previous estimates5-7.
Das PDF enhält zusätzlich einen Anhang von 10 Seiten
Gesehen am 14.05.2021